Advances in the Field of Micro- and Nanotechnologies Applied to Extracellular Vesicle Research: Take-Home Message from ISEV2021 - Silvia Picciolini; Francesca Rodà; Marzia Bedoni; Alice Gualerzi (Micromachines, 2021)
Extracellular Vesicles (EVs) are naturally secreted nanoparticles with a plethora of functions in the human body and remarkable potential as diagnostic and therapeutic tools. Starting from their discovery, EV nanoscale dimensions have hampered and slowed new discoveries in the field, sometimes generating confusion and controversies among experts. Microtechnological and especially nanotechnological advances have sped up biomedical research dealing with EVs, but efforts are needed to further clarify doubts and knowledge gaps. In the present review, we summarize some of the most interesting data presented in the Annual Meeting of the International Society for Extracellular Vesicles (ISEV), ISEV2021, to stimulate discussion and to share knowledge with experts from all fields of research. Indeed, EV research requires a multidisciplinary knowledge exchange and effort. EVs have demonstrated their importance and significant biological role; still, further technological achievements are crucial to avoid artifacts and misleading conclusions in order to enable outstanding discoveries.